Pathology Anatomy and Hemolymph Profile of Spiny Lobster (Panulirus homarus) Infested by Octolasmis sp. on Bottom Cage - Bahtiar, Sadida Anindya; Mahasri, Gunanti; Ulkhaq, Mohammad Faizal (Universitas Airlangga, 2024)
Spiny lobster, a fishery commodity with important economic value, is often infested by Octolasmis sp. on their bodies, which causes stress conditions that lead to death. This study aimed to determine the anatomical pathology and hemolymph profile of spiny lobster infested with Octolasmis sp. in bottom cages. The method used was an observation, where 30 lobsters (weight 112.44 ± 24.63 g) were carried out in June–July 2022 at the Pesona Bahari Wongsorejo, Banyuwangi. Hemolymph profile and anatomical pathology data were analyzed, respectively, using the Independent T-Test and Kruskal-Wallis test (α = 95%). The results based on scoring data showed a very significant difference between infected and healthy lobsters (p < 0.01), characterized by the occurrence of tail flakes, lesions on the carapace, gill melanization, and the appearance of ulcers on the ventral abdomen. A very significant change occurred in the hemolymph profile of infected lobsters compared to healthy lobsters (p < 0.01). Total hemocyte count increased with high concentrations of granular cells, respectively 22.1–37.8 ´x 106 cells/mL and 63.75–64.5%, along with lobster damage, while hyaline cells decreased. This study showed that there was a change in anatomic pathology and hemolymph profile between infected and healthy lobsters.